Animal models, treatment options, and biomaterials for female stress urinary incontinence - Tan, Xiyang; Li, Guangzhi; Li, Chenchen; Kong, Chenfan; Li, Huizhen; Wu, Song (Frontiers in Bioengineering and Biotechnology, 2024)
In the quest to tackle stress urinary incontinence (SUI), the synthesis of cutting-edge biomaterials and regenerative materials has emerged as a promising frontier. Briefly, animal models like vaginal distension and bilateral ovariectomy serve as crucial platforms for unraveling the intricacies of SUI, facilitating the evaluation of innovative treatments. The spotlight, however, shines on the development and application of novel biomaterials—ranging from urethral bulking agents to nano-gel composites—which aim to bolster urethral support and foster tissue regeneration. Furthermore, the exploration of stem cell therapies, particularly those derived from adipose tissues and urine, heralds a new era of regenerative medicine, offering potential for significant improvements in urinary function. This review encapsulates the progress in biomaterials and regenerative strategies, highlighting their pivotal role in advancing the treatment of SUI, thereby opening new avenues for effective and minimally invasive solutions.